Soybean Seed Treatment with Nickel Improves Biological Nitrogen Fixation and Urease Activity - Lavres, José; Castro Franco, Guilherme; de Sousa Câmara, Gil M. (Frontiers in Environmental Science, 2016)
Nickel (Ni) is an essential micronutrient required for plants’ metabolism due to its role as a structural component of urease and hydrogenase, which in turn perform nitrogen (N) metabolism in many legume species. Seed treatment with cobalt, molybdenum and Bradyrhizobium strains has been widely practiced to improve crops. Additionally, seed treatment together with Ni fertilization of soybean might improve the efficiency of biological nitrogen fixation (BNF), boosting grain dry matter yield and N content. The objective of this study was to evaluate the effect of soybean seed treatment with Ni rates (0, 45, 90,135, 180, 360 and 540 mg kg-1) on biological nitrogen fixation (BNF), directly by the 15N natural abundance method (δ15N‰) and by measurement of urease [E.C. 3.5.1.5] activity, as well as indirectly by nitrogenase (N-ase) activity [E.C. 1.18.6.1]. Soybean plants (cultivar BMX Potência RR) were grown in a sandy soil up to the R7 developmental stage (grain maturity), at which point the nutrient content in the leaves, chlorophyll content, urease and N-ase activities, Ni and N content in the grains, nodulation (at R1 - flowering stage), as well as the contribution of biological nitrogen fixation (δ15N ‰), were evaluated. The proportion of N derived from N2 fixation varied from 77 to 99% using the natural 15N abundance method and non-nodulating Panicum miliaceum and Phalaris canariensis as references. A Ni rate of 45 mg kg-1 increased BNF by 12% compared to the control. The increased N uptake in the grains was closely correlated with chlorophyll content in the leaves, urease and N-ase activities, as well as with nodulation. Grain dry matter yield and aerial part dry matter yield increased, respectively, by 84% and 51% in relation to the control plants at 45 mg kg-1 Ni via seed treatment. Despite, Ni concentration was increased with Ni-seed treatment, Ni rates higher than 135 mg kg-1 promoted negative effects on plant growth and yield. In these experimental conditions, seed treatment with low Ni rates caused higher dry matter yield of plants and grains.